Vaccination in childhood: health education video for parents and guardians - Viviane Nogueira Borges Trajano; Paola Cristina de Castro; Silvia Matumoto; Tauani Zampieri Fermino; Luciana Mara Monti Fonseca; Gloria Lúcia Alves Figueiredo; Angelina Lettiere-Viana (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To develop, validate, and evaluate an educational video on childhood vaccination for parents and guardians. Method: Methodological study in three phases. Pre-production included: script, storyboard, recruitment and validation by experts. During production, the video was created and validated by experts and the target audience. In post-production, the video was edited. The experts consisted of 20 health workers, professors and researchers (child health, immunization, health education and video production). The target audience consisted of 11 parents and guardians. Instruments were used for experts and the target audience and submitted to Content Validity Index analysis, with a minimum parameter of 0.80 for validity and evaluation. Results: The video, lasting 4 minutes and 25 seconds, was considered validated by experts and evaluated by parents and guardians, with an Overall Content Validity Index of 0.99 and 1.00, respectively. All validation and evaluation items obtained indexes equal to or greater than 0.95. Conclusion: The educational video developed was considered validated by experts and evaluated by the target audience, serving as a tool to encourage parents and guardians to promote child health and reduce vaccine-preventable diseases.